Synthesis of Ca-Psz nanoparticles using sol-gel technique with chitosan as a dispersant for raw materials restoration and dental rehabilitation equipment - Prameshwari, Fadilla Rizky; Karlina, Elin; Hasratiningsih, Zulia (Padjadjaran Journal of Dentistry, 2013)
Introduction: Zirconia (ZrO2) is a metal-free substance that rapidly improving as dental materials that has a good properties which are high biocompatibility, esthetics, and strength. Addition of a stabilizer like CaO will increase the mechanical properties of zirconia due to the transformation toughening. Methods: The Calcia Partially Stabilized Zirconia (Ca-PSZ) nanoparticles can be synthesized by using sol gel technique. This method makes easier to control the purity, homogeneity and physical characteristics at low temperature. This method consists of two stages, hydrolysis and condensation. The precursor were used  Zirconium Chloride (ZrCl4) with 0,1 M concentration and Calcia as stabilizer with 7% concentration. The addition of Calcia will help the tetragonal crystals forming at low temperature. Calcination temperature was used 900o C. To prevent conglomeration or agglomeration, dispersants are needed. One of the dispersants available is chitosan. Results: X-Ray Diffraction (XRD) analysis identifies that there are tetragonal and monoclinic phase with a percentage of 85% and 15% perspectively for sample without using chitosan and 100% tetragonal for sample that using chitosan. Analysis of Scanning Electron Microscope (SEM) results that particles with chitosan are more homogenous and dispersed with smaller size produced compared to particles without chitosan. Conclusion: From the results of the analysis, Ca-PSZ with sol-gel technique can produce nanoparticle and addition of  chitosan  can dispersed nanoparticles that could be used as material restoration and rehabilitation component  in dentistry.